Prevalence of Oral Trichomonas tenax in Periodontal Lesions of Down Syndrome in Tabriz, Iran - Atabak Kashefi Mehr; Ali Zarandi; Keivan Anush (Journal of Clinical and Diagnostic Research, 2015)
Background: It was presented that Trichomonas tenax is one of the parasites which is responsible for oral infection. This study was considered to estimate the prevalence of this parasite in oral cavity of Down syndrome patients with periodontal lesions and in healthy population from welfare organization in Tabriz, Iran. Materials and Methods: In the case-control study, 52 patients with periodontal disease (case group) and 52 individuals with healthy gingiva (control group) selected for the study. Examination was done by dental mirror and periodontal probe. After using plaque detector tablets, sampling was done by entering sterile paper into periodontal pocket for 20 seconds. The amount of plaque was measured by plaque index. Finally samples sent to laboratory for prepared PCR reaction. Results: In the case group, 14 patients were infected and in the control group 5 individuals. Percentage of infection in case group was 18.8% and in the control group was 3% that difference was statically significant. Plaque index in the case group was 72 ± 10.2 and in the control group was 68 ± 11.4 and difference between two groups was not significant. Conclusion: Parasitic infections in Down syndrome were higher than healthy children while plaque index was not significantly different between the two groups. Therefore follow-up of orders are necessary in control of parasitic infection in Down syndrome that have intrinsic defect of immune systems.